An evaluation of milk recording, somatic cell counts and reproductive performance in a large cohort of dairy herds in England and Wales - Madouasse, Aurélien (2010)
Milk recording consists in the regular, usually monthly, collection of a milk sample from all the lactating cows of a dairy herd. A large sample of milk recording data collected in England and Wales between 2004 and 2006 was used in this thesis. A sample of 8,211,988 recordings in 2,128 herds, representing 16 % of the dairy herds in activity in December 2006, were described and analysed. Calvings followed a seasonal pattern with 80 % more calving in September than in May. Milk production was highest in May (26.5 kg) and lowest in October (24.1 kg). Butterfat was stable, close to 4 % from October to March and reached a minimum at 3.7 % in June and July. Protein stayed between 3.2 and 3.3 % all the year. Geometric mean somatic cell count was between 177 and 180 between October and March and reached 205,000 cells/mL in July and August. At the individual cow level, the mean milk yield, percentage of butterfat, percentage of protein, fat to protein ratio and somatic cell count (geometric mean) were 26.4 kg, 3.96 %, 3.29 %, 1.21 and 90,000 cells/mL, between 5 and 305 days in milk. Changes in individual cow somatic cell counts around a threshold of 200,000 cells/mL between consecutive recording dates were used to predict bulk milk somatic cell count at both the herd-year and test-day levels. The main contributors to bulk milk somatic cell counts were cows staying above the threshold for 2 consecutive test-days. Milk yields and composition at the start of lactation were used to predict the calving to conception interval. Higher milk yield, lower percentage of protein, lower percentage of lactose, higher somatic cell count and higher percentage of butterfat were associated with lower probabilities of conception before 145 days in milk.